Genetic diversity of strawberry cultivars in Banyuroto, Magelang, Indonesia based on Cleaved Amplified Polymorphic Sequence (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Arif MF, Aristya GR, Kasiamdari RS. 2019. Genetic diversity of strawberry cultivars in Banyuroto, Magelang, Indonesia based on Cleaved Amplified Polymorphic Sequence. Biodiversitas 20: 1721-1728. Banyuroto Village, Magelang, Central Java is the center of strawberry (Fragaria spp.) development and cultivation program. The mild climate makes the location very suitable for developing sub-tropic horticulture such as strawberry. Various kinds of cultivars have been developed as part of the agrotourism program. However, genetic variation research of those cultivars is still rarely done. Therefore, the molecular study of strawberry was conducted to determine the genetic variation using CAPS markers. DNA of Five strawberry cultivars from Banyuroto and seven strawberry cultivars from Indonesian Citrus and Subtropical Fruits Research Institute, Malang were isolated using the CTAB method. DNA amplification was performed by PCR using four pairs of primers named APx, OLP, F3H2, and CTI2. The amplification results were cut with three kinds of restriction endonuclease enzymes named MboI, MluI, and TaqI. Restriction product was used to analyze the genetic variation of twelve cultivars and to construct the dendrogram using MVSP software with the UPGMA algorithm. The result showed that the percentage of polymorphic was 45% from 9 polymorphic bands. Dendrogram result showed that there were four clusters. Cluster A consists of Stroberi Hitam, Cluster B consists of Californica Cultivars, cluster C consists of Osso Grande and Osso Purbalingga cultivars, and cluster D consists of Rosalinda, Deeprose, Dorit, Earlibrite, Tristar, Festival, Brastagi, and Aerut. This research concluded that CAPS markers can be used as a method for study genetic diversity of strawberries.
Keywords: CAPS, Fragaria, genetic variation, molecular markers, strawberry, restriction enzyme